Herbs Smart Farming System using Internet of Things (IoT) - Abd Razak, Mohammad Fared; Ubin, Aizan (Evolution in Electrical and Electronic Engineering, 2022)
Smart Herbs Hydroponic using (IoT) was developed to provide oversight to the gardener to start hydroponic crops on a medium or commercial basis. The development of this system through the ThingSpeak platform allows water pH level data and Electric Conductivity (EC) in the salt concentration in the nutrient solution to be stored in an online database. The developed hardware system consists of a pH sensor and an EC sensor. The sensor is able to detect value changes and restabilize the water condition by going through three stages. In state 1 EC levels below 1.4 mS/cc and pH values above 6.6 can only be compensated for by adding nutrient solution to the solution. In state 2, If the EC level is measured above 1.4 mS/cm and the pH level is measured above 6.6 and the solution system would add pH down to make the water more acidic. Lastly state 3, no solution would be added if the EC value is above 1.4 mS/cm and the pH value is below 6.6. The results of this project show that the change in water quality is due to plant nutrition and the mixing of foreign matter into the nutrient solution. The level of water quality can be characterized by several categories; 1.5 to 2.0 can be classified as good, below 1.5 and above 2.0 can be classified as harmful to herbaceous crops. For future proposals, this system may be, supplemented with roof control to prevent solution nutrients from mixing with foreign objects such as rainwater. Additional to this, LED lighting can be used in photosynthesis planting, converting this system into an indoor system.